The Instrumental Tango in Colombia : Adaptation and Composition in two Quintets of Bogotá and Medellín (Revista del Instituto de Investigación Musicológica "Carlos Vega", 2019)
In the present work the instrumental tango in Colombia and its processes of adaptationand composition are characterized through the experience of the Quinteto LeopoldoFederico from Bogotá and F-31 Quinteto from Medellín. In the first part of thearticle, the musical trajectory of the quintets is reviewed and the presence of tango inColombia is outlined having in mind the globalization of the genre. In the secondpart, 3 pieces composed by the groups are analyzed under the relationship betweenthe River Plate tango and the Colombian national music.
Keywords: Instrumental Tango; Tango Musical Culture; Tango in Colombia; New Composers